2018
DOI: 10.21037/jtd.2017.12.131
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a prognostic marker in acute respiratory distress syndrome patients: a retrospective study

Abstract: The NLR is potentially a predictive prognostic biomarker in ARDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 26 publications
2
71
0
3
Order By: Relevance
“…Data presented as mean (range), mean ±standard deviation, or n(%), BMI, body mass index distress syndrome, community-acquired pneumonia and sarcoidosis and tuberculosis. [13][14][15][16][17] In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group. The NLR in patients with profusion category 1 was also higher than controls; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Data presented as mean (range), mean ±standard deviation, or n(%), BMI, body mass index distress syndrome, community-acquired pneumonia and sarcoidosis and tuberculosis. [13][14][15][16][17] In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group. The NLR in patients with profusion category 1 was also higher than controls; however, the difference was not significant.…”
Section: Discussionsupporting
confidence: 50%
“…NLR has been shown to be an independent prognostic factor in several types of tumours, including colorectal, lung, breast, pancreatic, gastric and ovarian cancer . Studies have also shown a correlation between the NLR and the prognosis and severity of the clinical course in pulmonary diseases such as chronic obstructive pulmonary disease, acute respiratory distress syndrome, community‐acquired pneumonia and sarcoidosis and tuberculosis . In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group.…”
Section: Discussionsupporting
confidence: 49%
“…The NLR is calculated as the absolute neutrophil count divided by the absolute lymphocyte count, while the PLR is calculated by platelet count divided by absolute lymphocyte count. In the recent years, NLR and PLR have been validated as prognostic markers in various disorders such as cardiac conditions, solid tumors, sepsis, pneumonia, and acute respiratory distress syndrome (ARDS) [8][9][10][11][12][13]. Few studies have evaluated the role of NLR and PLR in patients with severe and non-severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that NLR and other haematological markers of the systemic inflammatory response can reliably predict inflammatory response and survival in patients with malignancy. 9 – 14 Many groups have investigated the prognostic value of the NLR in a variety of inflammatory diseases at differing stages of disease. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“… 7 The NLR is calculated by dividing the neutrophil count by the lymphocyte count. 8 NLR is already used as an easily accessible inflammatory marker in adults with acute respiratory distress syndrome, 9 spontaneous bacterial peritonitis, 10 ischaemic heart disease, metabolic disease, cancer and other medical conditions. 11 In children, NLR can differentiate between viral and bacterial pneumonia, 12 , 13 and it can be a useful diagnostic marker of acute appendicitis and acute infection.…”
Section: Introductionmentioning
confidence: 99%